2015
DOI: 10.1037/a0038374
|View full text |Cite
|
Sign up to set email alerts
|

Examining the longitudinal association between oppositional defiance and autonomy in adolescence.

Abstract: In this longitudinal study, we tested whether the association between oppositional defiance to parental authority (i.e., adolescents' tendency to bluntly reject parental rules) and autonomy would depend upon the specific conceptualization of autonomy. Whereas oppositional defiance would yield more interpersonal distance from parents, because it involves turning away from parental authority, it would also yield less volitional functioning, as oppositional defiance would come at the expense of acting upon one's … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
44
1
8

Year Published

2015
2015
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 48 publications
(53 citation statements)
references
References 62 publications
0
44
1
8
Order By: Relevance
“…They oppose each other, lose engagement, and move toward a lower‐quality motivating style. As relationship partners lose autonomy, agency, and autonomy support (replaced by compulsions, compliance, and control), the two function in diminished ways (i.e., poor internalization, ill‐being, compromised relationship functioning, interpersonal distance, oppositional defiance; Costa et al, ; Van Petegem, Vansteenkiste, Soenens, Beyers, & Aelterman, ; Vansteenkiste, Soenens, Van Petegem, & Duriez, ). The two become motivational and environmental liabilities to each other.…”
Section: Reciprocal Causationmentioning
confidence: 99%
“…They oppose each other, lose engagement, and move toward a lower‐quality motivating style. As relationship partners lose autonomy, agency, and autonomy support (replaced by compulsions, compliance, and control), the two function in diminished ways (i.e., poor internalization, ill‐being, compromised relationship functioning, interpersonal distance, oppositional defiance; Costa et al, ; Van Petegem, Vansteenkiste, Soenens, Beyers, & Aelterman, ; Vansteenkiste, Soenens, Van Petegem, & Duriez, ). The two become motivational and environmental liabilities to each other.…”
Section: Reciprocal Causationmentioning
confidence: 99%
“…For instance, when they consider following rules to be ‘for teachers’ pets’, they feel pressured by an inner voice to not comply with these rules as to prove to themselves they do not belong to such a category of students. Regardless of whether students’ defiance of rules is grounded in more external or internal demands, it reflects the tendency to seek distance from the teacher (Van Petegem et al ., ). Because defiance is not based upon self‐endorsed values and choices but instead is determined by external or internal pressures they oppose, it can be conceived as a form of anti‐internalization.…”
Section: Introductionmentioning
confidence: 97%
“…Yet, a lack of motivation may also take the form of oppositional defiance, as when students feel either externally or internally pressured to refrain from rule compliance (Aelterman et al ., ). Indeed, when students are exposed to pressuring circumstances, they may also react with more active forms of non‐compliance (Van Petegem, Soenens, Vansteenkiste, Beyers, & Aelterman, ). Specifically, the presence of an overly demanding teacher or the pressure to save face in front of peers constitute examples of external pressure that may put students at risk for a power game with their teacher to maintain or establish their independence.…”
Section: Introductionmentioning
confidence: 99%
“…The dissemination of this knowledge may change the focus of Jamaican parents away from suppressing resistance to guiding children’s development of skills to express themselves in a socially competent manner. Van Petegem et al (2015) found that only unskillful oppositional forms of non-compliance are associated with negative outcomes for children.…”
Section: Discussionmentioning
confidence: 97%